2019
DOI: 10.1051/matecconf/201926603004
|View full text |Cite
|
Sign up to set email alerts
|

Retention factors of experienced Malay male Architects in Malaysian architectural design consultant firms in the Klang Valley, Malaysia

Abstract: The Malaysian construction industry suffers from a high rate of talent attrition within architecture design consultant firms which hinders these firms from competing locally and globally. This talent attrition hinders strategic nurturing of employees needed to sustain the firms’ involvement in the global market. This paper reports the findings of an investigation into the factors that contribute to employee retention of a purposive sample of ten male professional Malay Architects in Malaysian architecture cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Organizational commitment (employee loyalty) ranked fourth out of the 12 factors. The findings indicated a high level of loyalty and professionalism among construction personnel, similar to the past research of Mohd Amar & Ariffin (2019), employees in the architectural design consultant firm are unlikely to leave their jobs due to their commitments to execute the tasks assigned by their managers and subordinates. Respondents in this study also agreed that loyalty is a human characteristic of humankind.…”
Section: Data Analysis and Discussion Of The Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Organizational commitment (employee loyalty) ranked fourth out of the 12 factors. The findings indicated a high level of loyalty and professionalism among construction personnel, similar to the past research of Mohd Amar & Ariffin (2019), employees in the architectural design consultant firm are unlikely to leave their jobs due to their commitments to execute the tasks assigned by their managers and subordinates. Respondents in this study also agreed that loyalty is a human characteristic of humankind.…”
Section: Data Analysis and Discussion Of The Resultssupporting
confidence: 82%
“…The findings are comparable to Alias et al (2019), who revealed that ICT professionals prefer reliable connections with their superiors to help them improve their overall well-being at work, e.g., by aiding them in solving issues or obtaining resources to accomplish tasks. This survey's results also discovered that open communication and networking events among workers may be used to build a positive relationship between workers, and the respondents in this survey have the same opinion as the previous literature (Nguyen, 2020;Mohd Amar & Ariffin, 2019). Respondents also agreed that transparent, fair, and supportive relationships between managers and colleagues improve their job satisfaction, and management style and leadership do have a significant impact on their commitment to the company.…”
Section: Data Analysis and Discussion Of The Resultssupporting
confidence: 57%
See 2 more Smart Citations